PENGARUH KEPEMILIKAN MANAJERIAL, FINANCIAL DISTRESS, RISK AUDIT TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) PERIODE 2022-2023 - Desi Astuti, Tika; Budiantara, Martinus (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the effect of managerial ownership, financial distress, and risk audit on audit report lag (an empirical study of manufacturing companies listed on the Indonesia Stock Exchange) for the period 2022-2023. This study uses a quantitative approach with secondary data. The techniques used in this study are t-test analysis and multiple regression analysis. The research sample consisted of 28 companies listed on the Indonesia Stock Exchange (IDX) selected using purposive sampling based on predetermined criteria. The data analysis used SPSS version 26.0 for Windows. The results of this study indicate that: (1) managerial ownership affects audit report lag; (2) financial distress affects audit report lag; (3) audit risk does not affect audit report lag. Recommendations from this study include that future researchers should add other variables that may affect audit report lag, such as company operational complexity, auditor industry specialization, or audit committee size, and so on.